A hybrid approach for the assessment of outdoor thermal comfort. (March 2019) - Mijorski, Sergey; Cammelli, Stefano; Green, Johnathan
Abstract: With a constantly growing urban population, pressure on real estate has never been this high. The commercial and financial success of new residential developments is often linked to the ability of designers to deliver comfortable and pleasant outdoor spaces people can enjoy. Environmental parameters such as local wind speed, air temperature, humidity and incident solar radiation need to be taken into consideration during design. This is especially true for geographic regions where climatic conditions are far from temperate. This technical paper, making use of a case study project located in the Middle East, presents a hybrid approach for the assessment of outdoor thermal comfort, an approach where experimentally generated and numerically simulated data come together in synergy. Highlights: A hybrid approach for the assessment of outdoor thermal comfort. The Universal Thermal Climate Index for every hour throughout a typical year. Evaluating and validating mitigation measures impacting the microclimate. Modifying or re-assigning the daily schedules for specific outdoor activities.